An Algorithm for Surgical Approach to the Anterior Skull Base - Naunheim, Matthew R.; Goyal, Neerav; Dedmon, Matthew M.; Chambers, Kyle J.; Sedaghat, Ahmad R.; Bleier, Benjamin S.; Holbrook, Eric H.; Curry, William T.; Gray, Stacey T.; Lin, Derrick T. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objective To characterize our experience with the surgical management of anterior skull base malignancy, and to propose an algorithm for surgical approach to anterior skull base malignancies.Design Retrospective review.Setting Academic cranial base center.Participants Sixty-seven patients who underwent resection of paranasal sinus or anterior skull base malignancy with an endoscopic, cranioendoscopic, or traditional anterior craniofacial approach.Outcome Measures Complications, recurrence, and survival.Results There were 48 males and 19 females, ranging from 6 to 88 years old. There were three groups: endonasal endoscopic resection (n = 10), cranioendoscopic resection (n = 12), and traditional craniofacial resection (n = 45). The most common tumor pathologies included esthesioneuroblastoma, squamous cell carcinoma, and sinonasal undifferentiated carcinoma. Patients with T3/T4 disease were less likely to undergo endoscopic resection (p = 0.007). The 5-year disease-free survival was 82.1% overall, with no statistically significant differences among approaches. There were no differences in orbital complications, meningitis, or cerebrospinal fluid leak. Use of a transfacial incisions predisposed patients to surgical site infection and sinocutaneous fistulae. An algorithm for surgical approach was developed based on these results.Conclusion Sinonasal and skull base malignancies can be safely surgically addressed via several approaches. Surgical approach should be selected algorithmically based on preoperative clinical assessment of the tumor and known postoperative complication rates.
Keywords: skull base surgery; sinonasal malignancy; CSF leak; sinocutaneous fistula